(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper explores the multifaceted impact of trade wars on global economic performance, focusing on their implications for trade volumes, economic growth, employment, inflation, and international relations. Trade wars, characterized by the imposition of tariffs and trade barriers, disrupt established trading patterns and create significant economic uncertainty. The most prominent example in recent history is the U.S.-China trade war, which began in 2018 and led to widespread repercussions for both economies and the global market. The study highlights how trade wars can result in reduced global trade volumes, as nations impose tariffs that increase costs for consumers and businesses alike. These barriers not only lead to misallocation of resources but also slow economic growth, as reduced trade can hinder investment and productivity. Employment is affected unevenly; while certain industries may benefit from protectionist measures, others face job losses due to decreased demand for exports and increased production costs.